2020
DOI: 10.3390/cells9092100
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin as a Broad-Spectrum Host-Directed Antiviral: The Real Deal?

Abstract: The small molecule macrocyclic lactone ivermectin, approved by the US Food and Drug Administration for parasitic infections, has received renewed attention in the last eight years due to its apparent exciting potential as an antiviral. It was identified in a high-throughput chemical screen as inhibiting recognition of the nuclear localizing Human Immunodeficiency Virus-1 (HIV-1) integrase protein by the host heterodimeric importin (IMP) α/β1 complex, and has since been shown to bind directly to IMPα to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 50 publications
(152 reference statements)
6
62
0
1
Order By: Relevance
“…On this regard, the in vivo mouse model of MHV infection would not support a modulatory action of ivermectin on the immune response. On the other hand, these results are in accordance with various reports demonstrating that the broad-spectrum antiviral potential of ivermectin against several RNA viruses is due to its ability to specifically bind to and destabilize the importin α/β heterodimer, thereby preventing importin α/β from binding to the viral protein, which in turn blocks the nuclear trafficking of viral proteins (Jans and Wagstaff, 2020;Sharun et al, 2020;Caly et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…On this regard, the in vivo mouse model of MHV infection would not support a modulatory action of ivermectin on the immune response. On the other hand, these results are in accordance with various reports demonstrating that the broad-spectrum antiviral potential of ivermectin against several RNA viruses is due to its ability to specifically bind to and destabilize the importin α/β heterodimer, thereby preventing importin α/β from binding to the viral protein, which in turn blocks the nuclear trafficking of viral proteins (Jans and Wagstaff, 2020;Sharun et al, 2020;Caly et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…IVM is an approved drug for treatment of rosacea due to its antiparasitic properties complemented by anti-inflammatory activity [10][11][12]. In addition, the activity of IVM against various viruses [13], including COVID-19 [14,15], is of a special interest. Several clinical studies are planned or have been started for this indication [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have been reporting the broad-spectrum anti-parasitic drug ivermectin as a SARS-CoV-2 replication inhibitor (Caly et al, 2020), since other studies have reported many antiviral actions against HIV (Wagstaff et al, 2012;Caly et al, 2020;Heidary and Gharebaghi, 2020), DENV (Xu et al, 2018;Caly et al, 2020;Heidary and Gharebaghi, 2020), ZIKA (Caly et al, 2020;Heidary and Gharebaghi, 2020), and Influenza A (Götz et al, 2016;Heidary and Gharebaghi, 2020). This drug is a macrocyclic lactone with its main antiviral mechanism of action in the nuclear transport role of the host importin α (IMPα) protein (Jans and Wagstaff, 2020;Schwemmle et al, 2020). Furthermore, one study has showed that this molecule presented antiviral effects against the SARS-CoV-2 in vitro assays with Vero/ hSLAM cells with 5000-fold reduction in viral RNA after 48 h with IC50 varying from 2.2 to 2.5 μM (Caly et al, 2020;Sharun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%